2017
DOI: 10.1245/s10434-017-6296-2
|View full text |Cite
|
Sign up to set email alerts
|

STMN1 is Overexpressed in Adrenocortical Carcinoma and Promotes a More Aggressive Phenotype In Vitro

Abstract: STMN1 is overexpressed in human ACC samples, and knockdown of this target in vitro resulted in a less aggressive phenotype of ACC, particularly under serum-starved conditions. Further study is needed to investigate the feasibility of interfering with STMN1 as a potential therapeutic target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 31 publications
4
8
0
Order By: Relevance
“…Alterations in the expression of β-tubulin isotypes and apoptotic regulatory proteins such as XIAP and MAPs (microtubule-associated proteins) regulated PTX activity in different types of cancers 12 , 15 , 20 , 30 . For example, drug-resistant cancer cells and human tumor tissues were shown to harbor tubulin gene mutations, alterations in total tubulin content, altered microtubule polymer levels, altered expression of tubulin isotypes, and altered microtubule-associated protein expression 13 , 14 , 21 , 28 , 30 . High expression of βIII-tubulin has been found to be correlated either with low response rates in patients treated with regimens containing taxanes or vinorelbine or with reduced survival in patients with NSCLC, breast, ovarian, and gastric cancers 40 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alterations in the expression of β-tubulin isotypes and apoptotic regulatory proteins such as XIAP and MAPs (microtubule-associated proteins) regulated PTX activity in different types of cancers 12 , 15 , 20 , 30 . For example, drug-resistant cancer cells and human tumor tissues were shown to harbor tubulin gene mutations, alterations in total tubulin content, altered microtubule polymer levels, altered expression of tubulin isotypes, and altered microtubule-associated protein expression 13 , 14 , 21 , 28 , 30 . High expression of βIII-tubulin has been found to be correlated either with low response rates in patients treated with regimens containing taxanes or vinorelbine or with reduced survival in patients with NSCLC, breast, ovarian, and gastric cancers 40 .…”
Section: Discussionmentioning
confidence: 99%
“…The degradation was a proteasome-dependent, rapid and irreversible process initiated by tubulin aggregation 24 . Some studies showed that XIAP, Tau, Hsp70 partly were degraded by 26S proteasome 25 28 . Here SFN-Cys and SFN-NAC induced the degradation of XIAP, Tau, Hsp70, Stathmin1 via upregulating 26S proteasome, and the effects of degradation were reversed by 26S proteasome inhibitor MG132.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the mitotic interval, the active state of STMN1 protein promotes microtubule depolymerization. 17 The expression level of STMN1 in tumors is directly related to the prognosis of patients, and the expression of stathmin protein in tumor cells affects the sensitivity of vinblastine and paclitaxel drugs. 18 Based on the above evidence, LINC01116 plays a critical role in tumor development.…”
Section: Introductionmentioning
confidence: 99%
“…Somatically, dysregulation of protein kinase A and mutations in ADIPOR1 , ADIPOR2 , APC , ARMC5 , SDHA , SDHC , SF1 , and IGF2 , among others, have also been implicated as mediators of ACC tumorigenesis, along with mutations in RB1 and APC (Babińska et al 2017; Else et al 2017). Recent expression studies have identified sonic hedgehog and somatostatin receptor pathways activated in ACC, along with markedly increased expression in cytosolic protein Stathmin1, SLC12A7 and phospho-mTOR, EGFR, and WNT/β-catenin signaling pathways (Germano et al 2017; Aronova et al 2018; Brown et al 2018a,b; Hasanovic et al 2018). At the miRNA level, miR-483-3p and miR-139-5p promote ACC aggressiveness (Agosta et al 2018).…”
Section: Introductionmentioning
confidence: 99%